Rearrange the equation so x is the independent variable. y +6 = 5(x-4) y =​

Question

Rearrange the equation so x is the independent variable.
y +6 = 5(x-4)
y =​

in progress 0
Katherine 2 weeks 2021-09-15T08:11:20+00:00 2 Answers 0

Answers ( )

    0
    2021-09-15T08:12:34+00:00

    Answer:

    y=5x-26

    Step-by-step explanation:

    y+6=5(x-4)

    -> y+6=5x-20

    -> y=5x-20-6

    therefore, y=5x-26

    0
    2021-09-15T08:13:17+00:00

    Answer:

    y=5x-26

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )